AXIOLOGICAL ANALYSES OF PHRASEOLOGICAL UNITS WITH COLOR COMPONENTS IN ENGLISH LANGUAGE - Z.Isakova; J. Azimov (University Research Base, 2024)
This article presents an axiological analysis of phraseological units (PUs) with color components in the English language, revealing the deep-seated values, emotions, and cultural attitudes embedded within linguistic expressions. By examining a spectrum of colors – red, blue, green, white, and black–embedded in idioms, proverbs, and fixed expressions, the study highlights how colors transcend their literal and aesthetic dimensions to embody complex evaluative and connotative meanings. The investigation employs a multimodal methodological approach, combining qualitative analysis of cultural, historical, and emotional contexts with quantitative analysis of the distribution and frequency of color-based PUs across various text genres. The findings underscore the significance of color in English phraseology as a vehicle for expressing a wide array of human experiences, emotions, and cultural narratives. This axiological perspective not only deepens our understanding of the emotive and connotative power of language but also illustrates the pervasive role of cultural values in shaping linguistic expressions. The study contributes to the broader field of linguistic axiology, offering insights into how language reflects and constructs the values and attitudes of society through the prism of color.